Determinants of Information Security Awareness and Behaviour Strategies in Public Sector Organizations Among Employees - Al-Shanfari I; Warusia Yassin; Nasser Tabook; Roesnita Ismail; Anuar Ismail (Science and Information (SAI) Organization, 2024)
Indexed by WOS/Scopus/ERA